Needle capsulorhexis in intumescent white cataract using slow injecting viscoelastic device through an anterior chamber maintainer - Rahar, S; Sethi, H; Sethi, H; Gupta, VS (Nepalese Journal of Ophthalmology, 2011)
DOI: http://dx.doi.org/10.3126/nepjoph.v3i2.5282Nepal J Ophthalmol 2011; 3(2): 214-215